P75 Anti-SSA/Ro positivity and the risk of congenital heart block: obstetric and fetal outcome in a cohort of anti-SSA/Ro positive pregnant patients with and without autoimmune diseases. (23rd March 2020) - Fredi, Micaela; Gerosa, Maria; Andreoli, Laura; Vojanovic, Tamara; Chighizola, Cecilia Beatrice; Gazzola, Federica; Lojacono, Andrea; Zatti, Sonia; Trespidi, Laura; Ferrazzi, Enrico; Caporali, Roberto; Meroni, PierLuigi; et al.
Abstract : Background: Neonatal lupus syndrome is an acquired disease caused by the transplacental passage of anti-SSA/Ro antibodies. Congenital heart block (CHB) represent the most serious manifestation. The rate of CHB in anti-SSA/Ro positive pregnant woman varies among studies ranging from 1 to 5% in different populations. Aim of our study was to assess the prevalence of CHB in a cohort of anti-SSA/Ro positive pregnant women prospectively followed up in 2 Italian tertiary referral centers. Methods: Patients underwent monthly clinical examination and data regarding the disease and pregnancy course were recorded. Moreover, fetal heart rates were assessed weekly by Doppler ultrasound from the 14th to the 26th gestational week. Results: Between 2010 and 2018 we recorded data of 286 pregnancies, with the following maternal diagnosis: SLE in 73 (25.3%), Sjogren Syndrome in 52 (18%), undifferentiated connective tissue disease in 59 (20.6%), asymptomatic Ro/SSA carriers in 50 (17.4%) and other connective tissue disease in the remaining. In 5 pregnancies (1.7%) a third-degree CHB was diagnosed. In all these 5 pregnancies, anti-SSA/Ro positivity was established after CHB detection and the mothers were initially labeled as SSA/Ro carriers. Conclusions: Even if the incidence of CHB as a whole was comparable to that reported in previous studies, none of the pregnancies prospectively followed before and during pregnancy developed CHB. These data suggest that a strict follow up and proper treatment of anti-SSA/Ro positive patients with an established autoimmune disease before and during pregnancy can reduce the risk.